Global technological change impact on female textile and garment workers in Thailand - Islam, Nazrul; Swierczek, Fredric William (BRAC University, 2010)
Global technological change has significant impact on lower skilled female textile and garment workers in Thailand, as it brings new machines and manufacturing processes into the company. This study aims at identifying the factors of global technological change on female textile and garment workers in Thailand. It covers three impact areas such as, job security, job satisfaction and work relations. 10 variables were identified from job security, 36 from job satisfaction and 10 from work relations’ areas. Multivariate analysis such as, Factor Analysis and Multiple Regression was used to analyze the data. Factor Analysis has been performed to identify the factors of the technological change on the female workers. Using Multiple Regression analysis, the overall impact of the technological change on female textile and garment workers has been assessed. The results show that the impact factors are frustration, skill demands, downsizing, meaningful work, pride in job, supervision, benefits, bureaucracy, unclear work assignments, recognition, fairness in pay, workload, the change process, strikes, and personal control. Among these factors, frustration and downsizing are concerned with job security; benefits, bureaucracy are related to job satisfaction; and the work processes and personal control are concerned with work relations. These factors are significantly related to the overall impact of the technological change on Thai female textile and garment workers. Factors concerning job security, job satisfaction, work relations together are significantly related to the overall socioeconomic lives of female and garment workers in Thailand.